2016
DOI: 10.21276/aimdr.2016.2.6.og1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Induction of Labor: A Prospective Study

Abstract: Background: Induction is defined as artificial initiation of uterine contraction with the aim of achieving the normal vaginal delivery. It is most widely accepted obstetrical intervention worldwide. The most common indication for induction is post dated pregnancy. Objective: To assess the outcome of induction in both mother and baby. Methods: During our study period, 391 patients were selected for induction due to various indications. Most of them were induced with tablet Misoprostol and only those with higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…The Incidence of induction across different settings varies from 5 to 22% of all labor room admissions. [1][2][3] Induced labor is artificial stimulation of uterine contractions before the onset of labor, any time after the fetus attains viability with the main aim to achieve vaginal birth. 4 Pharmacological modes of induction of labor include prostaglandins (per oral or intra-vaginal or intra-cervical) and oxytocin .Successful induction of labor is related to the condition or state of the cervix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Incidence of induction across different settings varies from 5 to 22% of all labor room admissions. [1][2][3] Induced labor is artificial stimulation of uterine contractions before the onset of labor, any time after the fetus attains viability with the main aim to achieve vaginal birth. 4 Pharmacological modes of induction of labor include prostaglandins (per oral or intra-vaginal or intra-cervical) and oxytocin .Successful induction of labor is related to the condition or state of the cervix.…”
Section: Introductionmentioning
confidence: 99%
“…4 Induction of labor with the help of prostaglandins offer the advantage of promoting cervical ripening along with stimulating the contractility of the myometrium. [1][2][3] The indications for Induction has increased so much in modern obstetrics to avoid the slightest risk to baby or mother that we are electively inducing labor at 39 weeks of pregnancy; though we know that induction is carried out routinely in postdated pregnancies. Many studies have indicated that about 10% of pregnancies remain undelivered beyond 42 weeks, so timely induction remains an important statement to bring out better labor outcomes in both baby and mother.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for considering induction are many and vary from obstetrician to obstetrician and from country to country [8]. The most common indication that requires induction of labor is postdated pregnancy [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Another frequently cited indication is term premature rupture of membrane [12,13,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the hypertensive disorder remains a rare indication, rather this requires induction in higher rate [14,20,21,25,26]. The less frequent indications are oligohydramnios, IUGR, gestational diabetes, fetal distress, macrosomia, fetal death, decreased fetal movement, uncomplicated twins, polyhydramnios, Rh isoimmunization, chorioamnionitis, heart disease, and other fetal indications [9][10][11][12][13][14]. In a meta-analysis, it is also observed that the common indications cited by many researchers are post-term pregnancy, PROM, oligohydramnios, twins, macrosomia, preeclampsia, diabetes, and IUGR [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation